2011
DOI: 10.1029/2010ja015776
|View full text |Cite
|
Sign up to set email alerts
|

Pi1B pulsations as a possible driver of Alfvénic aurora at substorm onset

Abstract: [1] Ground-based observations have shown Pi1B magnetic pulsations are associated with substorm onset. These pulsations can also be observed at geosynchronous orbit, suggesting that they propagate from (or beyond) geosynchronous orbit to the ionosphere at substorm onset. Independently, investigations have shown that the initial brightening of an arc at subtorm onset is Alfvénic in nature (i.e., that the aurora during the initial brightening is wave-driven). These results raise the question of whether Pi1B pulsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Strong Alfvenic turbulence is commonly observed in the PSBL at 4–6 R E geocentric distance with the Polar spacecraft during the expansion phase of substorms [ Wygant et al ., ; Keiling et al ., ]. Lessard et al [] found a relationship between Pi1B pulsations originating from beyond geosynchronous orbit and wave‐driven aurora during the onset of a substorm, suggesting that the pulsations propagating from the magnetotail are powering the aurora. Pi1B pulsations are bursty waves with frequencies from 25 mHz to 1 Hz; sometimes higher frequencies are seen too.…”
Section: Discussionmentioning
confidence: 99%
“…Strong Alfvenic turbulence is commonly observed in the PSBL at 4–6 R E geocentric distance with the Polar spacecraft during the expansion phase of substorms [ Wygant et al ., ; Keiling et al ., ]. Lessard et al [] found a relationship between Pi1B pulsations originating from beyond geosynchronous orbit and wave‐driven aurora during the onset of a substorm, suggesting that the pulsations propagating from the magnetotail are powering the aurora. Pi1B pulsations are bursty waves with frequencies from 25 mHz to 1 Hz; sometimes higher frequencies are seen too.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of the discharging current is beyond the scope of this paper, but it is emphasized that as mentioned earlier, the acceleration process of the UL electrons is expected to be different from that of the DD current (Karlsson 2012). In this regard, Mende (2003) found that the field-aligned current associated with the poleward advancing arc is carried by superthermal electrons accompanied by waves, which may be related to Pi1B pulsations (Lessard et al 2011). …”
Section: Deflationmentioning
confidence: 99%
“…KAWs have been found in the plasma sheet associated with fast flows (Angelopoulos et al, 2002;Chaston et al, 2009Chaston et al, , 2012, at the plasma sheet boundary layer (PSBL; Gershman et al, 2017;Wygant et al, 2002), and in the inner magnetosphere (Chaston et al, 2006(Chaston et al, , 2014Huang et al, 1997). It has been argued that Journal of Geophysical Research: Space Physics 10.1029/2019JA027062 the KAWs observed around the tail plasma sheet carry sufficient Poynting flux flowing along magnetic field lines toward the ionosphere to power low-altitude auroral acceleration (Angelopoulos et al, 2002;Lessard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%